APPLICABILITY OF THE INTERNET OF THINGS TO INCREASE PRODUCTIVITY AND INDUSTRIAL EFFICIENCY: case study with a furniture industry based in Taquaritinga-S`P - da Silva, Eunice Estevão Francisco; de Assis, Diego Edson; Del Vechio , Gustavo Henrique (Revista Interface Tecnológica, 2023)
The Internet of Things is one of the pillars of the Industry 4.0 concept, as it allows machines to communicate in an industrial environment and generate a wealth of data to ensure both production efficiency and bases for more assertive management decision-making. In this sense, this study proposes to study more deeply the concept of Internet of Things and its advantages for the industrial environment. Soon after, from a case study, it verifies how this concept has been used by a furniture industry to modernize its processes and guarantee much more efficiency in its production line, as well as more efficient communication between its sectors. What can be observed, based on these theoretical analyzes and the practical study, is that the Internet of Things helps to considerably reduce machinery downtime, as well as to enhance the efficiency of each asset on the factory floor. It becomes, therefore, fundamental for companies that want to produce more and remain in the spotlight in the market.
Keywords: Internet of Things; Industry 4.0; Industrial processes; Technology